Conditional Grants, Grant-Seeking and Welfare when there is Government Failure on the Subordinate Level - Ivo Bischoff (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
The paper addresses the welfare implications of conditional grants if government failure leads to inefficiencies in the production of regional public goods and services. Conditional grants may improve welfare by setting incentives for regions to improve efficiency. At the same time, resources are wasted in the process of grant-seeking. This paper provides a theoretical model to assess the net effect on welfare. A three-stage game-theoretic context is developed and simulations are performed to derive the optimal grant-distribution scheme. We found conditional grants to be welfare-enhancing in the vast majority of simulated scenarios under a classical utilitarian welfare function. Once distributional concerns are accounted for, the scope for conditional grants becomes limited.
Keywords: H77; H5; H11; D7; 330; conditional grants; government failure; rent-seeking; normative public finance; Finanzausgleich; Öffentliches Gut; Regionalverwaltung; Standortwettbewerb; Rent Seeking; Wohlfahrtseffekt; Theorie; Zweckzuweisung